Heritage Redemption and the Curse of Tourism: The Case of World's Last Inhabited Troglodyte Village. Issue 1 (2nd January 2021) - Alipour, Habib; Rezapouraghdam, Hamed; Akhshik, Arash
ABSTRACT: Kandovan, an inhabited troglodyte village, is a historical heritage site that attracts one million visitors per year on average. The collision between authenticity, commodification, conservation and sustainable indigenous livelihood warrants an immediate intervention to preserve this heritage site. Recognizing the fresh dilemmas created by the unsustainable tourism growth, this study provides valuable implications for the preservation of unique heritage sites and indigenous people. For this study, the qualitative method based on an interview with indigenous dwellers utilized. The study draws upon complexity theory and socio-ecological systems framework to enhance our understandings of indigenous whose livelihood is at stake. The research revealed that indigenous dwellers as the main stakeholders have not been considered as equal partners in the management of the site. Furthermore, the lack of collective action towards a sustainable framework is threatening the viability of the site as a heritage asset. Theoretical and managerial implications are discussed.